Animating science communication: Measuring U.S. consumers’ recall about genetic modification with animated infographics - Jessica Holt; Alexa J Lamm; Kristin Gibson; Kevan Lamm; Jason D Ellis Ph.D.; Joy N Rumble (Journal of Applied Communications, 2020)
Genetic modification (GM) science is a complex and controversial topic that can instill uncertainty and fear into the minds of the individuals. While science research surrounding GM science in food has indicated no negative impact on the health of humans, consumer perception research has indicated a sense of skepticism and risk surrounding the issue. The Risk Information Seeking and Processing (RISP) model attempts to understand how individuals search for and process information about a subject with some associated level of risk. Infographics are a form of data visualization used to communicate complex ideas. Animation has been shown to garner greater attention from respondents through previous research in other areas of consumer engagement. Utilizing a quasi-experimental study, this research tested the use of a static and animated infographic to measure impact of respondents’ ability to recall key information visually portrayed about GM science. The current study found a statistically significant difference was found between the animated infographic treatment group and the respondents’ recall ability. Several demographic factors were explored to further understand how infographics are processed by respondents. Key findings in the current research suggest intentional implementation of animation may attend respondents’ attention to key details and information associated with complex issues surrounding GM science in food.
Keywords: infographics; genetic modification; animation; information recall